PELAKSANAAN PENEGAKAN HUKUM TINDAK PIDANA PERTAMBANGAN EMAS LIAR GOLONGAN B DI WILAYAH HUKUM KEPOLISIAN SEKTOR KAMPAR KIRI - Saputra, Rian Prayudi; Indra, Mexsasai; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Criminal acts of illegal gold mining is a criminal act or a crime is classified into a specific crime that is growing from year to year so that the negative impact for the community and the environmentPerpetrators of the crime of illegal gold mining is not only a legal entity, but is also done by people around the gold mine. in combating illegal gold mining, the police take some action that preventive and repressive measures to combat the crime of illegal gold mining.Based on the description above, the authors are interested in doing research with Title Implementation of Law Enforcement Crime Illegal Gold Mining Sector Police Jurisdiction In Kampar Kiri. In writing this essay aims to investigate the implementation of enforcement against illegal gold mining in the area of police law left kampar sector and aims to find out the efforts made to overcome the obstacles in the implementation of enforcement against illegal gold mining without consent in the jurisdiction of the Police Sector Kampar Kiri.In writing this essay, the writer uses sociological research methods. The nature of the research is descriptive, providing a clear and detailed picture of the implementation of the law enforcement criminal offense of illegal gold mining in the region law Kampar Kiri Police Sector. Results of research conducted qualitatively and using deductive method, the decomposition problem of the general to specific.From the results of this study concluded that the implementation of the enforcement of illegal gold mining criminal acts committed by the police left kampar sector has obstacles such as lack of awareness of the Community Law, Lack of Kampar Kiri sector police personnel, lack of means, facilities and equipment in the eradication illegal gold mining. In law enforcement, police Kampar Kiri should more preventive action, conduct legal counseling to the community. In law enforcement, police Kampar Kiri should more preventive action, conduct legal counseling to the community.Keywords : Implementation - Criminal Law Enforcement -Crime of Illegal Gold Mining